REVITALIZATION OF DA’WAH IN OVERCOMING OF MISSUNDERSTANDING AL-QURAN IN EARLY CHILDREN - Yusuf, Mochamad Aris; Anam, Hoirul; Supardi, Supardi; Mushariawan, Ilham (QAULAN: Journal of Islamic Communication, 2023)
Da'wah activities in Islam are an obligation that must be carried out by every Muslim without exception. However, the perpetrators of da'wah are also required to understand the object of da'wah, this statement has been applied by mothers in completing the blindness of the Qur'an in early childhood. Where the success of da'wah built by mothers, is not because they are good at processing the words that are used in their da'wah activities, but because of the da'wah methods that are built according to the needs of the mad'u or object recipients of the da'wah material. So, in this article we want to know how the da'wah method is used by mothers. The purpose of this study is to dismantle the success of da'wah built by mothers. The method in this study uses qualitative research of the Phenomenological type. The findings in this article have shown that mothers can build an effective da'wah movement and are able to overcome Al-Qur'an literacy in young children at the Fathur Rahman Mosque by using three da'wah methods that were developed, namely: First, the motivational da'wah method. The two methods of preaching reward. The three methods of preaching are singing and sima'i.